Design of Wind Speed Measurement System in Wind Tunnel Based on Pitot Tube - Yudha Nurfauzi Nugraha; Erwin Erwin; Slamet Wiyono (Fakultas Teknik Universitas Pancasila, 2024)
In the current era, the development of science in all aspects continues to change. The use of wind at this time is necessary for the efficiency of the energy used. The wind speed research method for this study utilizes experimental laboratory methods, specifically employing a Pitot tube measuring instrument to collect wind speed data. From the wind speed data obtained using a frequency of 25–50 Hz, there is only a slight difference between readings from a testometer with a pitot tube and only at frequencies of 39 Hz and 43 Hz, which have a visible difference. The graph indicates that the research was successful by comparing the readings on the testometer.